Insights into newborn health; Integrating anthropometric measurements and immunization status at community health center deliveries in rural India: An observational study - Ayub Khan; Hari Shankar; Priyanka Dua (Journal of Indira Gandhi Institute of Medical Sciences)
Introduction: Newborn health is crucial for long-term well-being and development, especially in rural India, where healthcare access is limited. This study integrates anthropometric measurements and immunization status during community health center delivery. Integrating these metrics is essential as it helps identify early growth issues and ensures timely vaccinations, which are vital for preventing malnutrition and vaccine-preventable diseases in a setting where healthcare resources are scarce, and follow-up care is often challenging. Materials and Methods: The present study is based on baseline data of a larger prospective follow-up study conducted from November 2022 to February 2024 in rural areas of North India, including newborns delivered through cesarean section or vaginal delivery. Data were collected using a semi-structured questionnaire including weight, height, head circumference, chest circumference, and mid-arm circumference of the newborns. Results: The study included 150 newborns, with the mean age of mothers and fathers being 25.27 ± 2.81 years and 29.01 ± 3.76 years, respectively. Immunization coverage was high for hepatitis B (Hep-B) (99.3%) and oral polio vaccine (OPV) (99.3%) but lower for Bacillus Calmette–Guérin (BCG) (74.7%). Strong correlations were found among the five anthropometric measurements, indicating consistent growth patterns. Conclusions: The study highlights the demographic characteristics and immunization coverage among newborns in rural India. Despite high coverage for Hep-B and OPV, the lower uptake of the BCG vaccine indicates gaps in immunization outreach. The strong correlations among anthropometric measurements suggest consistent growth patterns, reinforcing the need for integrating such assessments into routine care to monitor and support healthy development.